The psychobiotic revolution mood, food, and the new science of the gut-brain connection - Anderson, Scott C.; Cryan, John F.; Dinan, Timothy G. 195X- (National Geographic, 2017)
"Written by the leading researchers in the field, this information-rich guide to improving your mood explains how gut health drives psychological well-being, and how depression and anxiety can be relieved by adjusting your intestinal bacteria. This groundbreaking book explains the revolutionary new science of psychobiotics and the discovery that your brain health and state of mind are intimately connected to your microbiome, that four-pound population of microbes living inside your intestines. Leading medical researchers John F. Cryan and Ted Dinan, working with veteran journalist Scott C. Anderson, explain how common mental health problems, particularly depression and anxiety, can be improved by caring for the intestinal microbiome. Science is proving that a healthy gut means a healthy mind...and this book details the steps you can take to change your mood and improve your life by nurturing your microbiome"...